2018
DOI: 10.1186/s13068-018-1335-1
|View full text |Cite
|
Sign up to set email alerts
|

An NIRS-based assay of chemical composition and biomass digestibility for rapid selection of Jerusalem artichoke clones

Abstract: BackgroundHigh-throughput evaluation of lignocellulosic biomass feedstock quality is the key to the successful commercialization of bioethanol production. Currently, wet chemical methods for the determination of chemical composition and biomass digestibility are expensive and time-consuming, thus hindering comprehensive feedstock quality assessments based on these biomass specifications. To find the ideal bioethanol feedstock, we perform a near-infrared spectroscopic (NIRS) assay to rapidly and comprehensively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Multivariate predictive models constructed based on at-line or inline NIR spectroscopic analysis could be a valuable resource for high-throughput and inexpensive characterization of chemical and physical changes in lignocellulosic feedstocks during thermochemical or physico-chemical conversion processes (Li et al, 2018;Hwang et al, 2021). Previous research has shown that NIR analysis in the 900-1700 nm region could be coupled with chemometric approaches to predict the cellulose (R 2 0.92), hemicellulose (R 2 0.84), and lignin (R 2 0.71) contents of various types of lignocellulosic pellets like corn stover, rice straw, pine, mahogany, and rubber wood (Feng et al, 2018).…”
Section: Application Of At-line and Off-line Nir Spectroscopy For Hig...mentioning
confidence: 99%
See 3 more Smart Citations
“…Multivariate predictive models constructed based on at-line or inline NIR spectroscopic analysis could be a valuable resource for high-throughput and inexpensive characterization of chemical and physical changes in lignocellulosic feedstocks during thermochemical or physico-chemical conversion processes (Li et al, 2018;Hwang et al, 2021). Previous research has shown that NIR analysis in the 900-1700 nm region could be coupled with chemometric approaches to predict the cellulose (R 2 0.92), hemicellulose (R 2 0.84), and lignin (R 2 0.71) contents of various types of lignocellulosic pellets like corn stover, rice straw, pine, mahogany, and rubber wood (Feng et al, 2018).…”
Section: Application Of At-line and Off-line Nir Spectroscopy For Hig...mentioning
confidence: 99%
“…In recent years, near infrared (NIR)-based high-throughput spectroscopic techniques have been developed to monitor the output of pelleting and other downstream processing of lignocellulosic biomass (Edmunds et al, 2018;Feng et al, 2018;Li et al, 2018;Li et al, 2021). NIR spectroscopy works based on the absorption, emission, reflection, and diffusereflection of light in the region of 800-2,500 nm (e.g., 12,500-4,000 cm −1 ) (Ozaki et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…isoprenoid alcohol (IPA) pathway was used that focuses on the synthesis and subsequent IPAs phosphorylation. 0.6 g/L [ 48 ] Gaseous products Hydrogen Thermoanaerobacterium aotearoense Rice straw Deletion of Fd:NADP + oxidoreductase (nfnAB) 0.381–0.419 g/L [ 49 ] Hydrogen Escherichia coli Xylose and Glucose Deletion in gene ptsG (phosphotransferase system) for as well as ldhA and frdD 0.284 g/L [ 50 ] Hydrogen Chlamydomonas reinhardtii CO 2 Repression of the psbA (PSII D1 protein gene) 60% enhancement in hydrogen production [ 51 ] …”
Section: Metabolic Engineering For Biofuel Productionmentioning
confidence: 99%